Pollen data from Tenaghi Philippon (Greece) spanning the past 500 kyrs - Andreas Koutsodendris; Vasilis Dakos; William J Fletcher; Maria Knipping; Ulrich Kotthoff; Alice M Milner; Ulrich C Müller; Stefanie Kaboth-Bahr; Oliver A Kern; Laurin Kolb; Polina Vakhrameeva; Sabine Wulf; et al. (PANGAEA, 2023)
Palynological and X-Ray fluorescence (XRF) data from Tenaghi Philippon (Greece) were generated to reconstruct climate and environmental changes in the Mediterranean region during the past 500 kyrs. The analyses were carried out on peat drillcores from two locations, i.e., TP-2005 – 40° 58 extquotesingle 24.0” N, 24° 13 extquotesingle 25.2” E; TP-2009 – 40° 57 extquotesingle 39.5” N, 24° 16 extquotesingle 03.1” E. A total of 2347 palynological samples, taken every 2-5 cm from the 4–91 m composite depth, were prepared using standard palynological techniques. Pollen percentages were calculated on the number of pollen grains from terrestrial plants excluding Cyperaceae and Poaceae because of their natural over-representation at Tenaghi Philippon. The palynological results present relative abundances of tree pollen, tree pollen without Pinus, temperate taxa, Mediterranean taxa, montane taxa, pioneer taxa, shrubs, steppic taxa, herbs, helophytes, sum of Poaceae and Cyperaceae, aquatic taxa, spores and algae. The XRF core scanning was performed with an AVAATECH (GEN-4) scanner at 5 mm resolution using a 10 kV energy level without filter, a current of 200 mA, and a counting time of 10 s. The geochemical results include the Si normalised counts and the log(Ca/Fe) ratio.